Case Report: Unusual Varicella-Zoster Virus Meningoencephalitis With Meningomyelitis Mimicking Central Nervous System Leukemia - Tu, Ranran; Liu, Jianyang; Cheng, Fan; Weng, Weipin; Zhang, Hainan; Shu, Yi; Wu, Xiaomei; Hu, Zhiping; Zhang, Jie (Frontiers in Medicine, 2022)
Background Varicella-Zoster Virus (VZV) is a human pathogen from the α-subfamily of herpesviruses. In immunocompromised patients, VZV may produce disease of the central nervous system (CNS). Clinical manifestations of CNS infection with VZV are non-specific and can mimic other infectious and non-infectious diseases. Due to similar symptoms, CNS infection with VZV represents a diagnostic challenge. Here, we report a case of a patient who showed laboratory and imaging manifestations mimicking the neoplastic etiology. Case A 31-year-old man presented with a 3-day history of headache, 5-h of confusion, generalized tonic-clonic seizures, and transient fever. The patient has a history of acute myelogenous leukemia (AML). His cerebrospinal fluid (CSF) studies revealed markedly elevated protein (10.326 g/L) and atypical cells. Meanwhile, the MRI of brain, cervical, and thoracic spine was reported as extensive (frontal, parieto-occipital and temporal pachymeningeal, and falx cerebri) enhancement and irregular thickening. These examinations suggested a suspicion of CNS involvement of AML. However, based on further investigations with metagenomic next-generation sequencing, a final diagnosis of VZV meningoencephalitis with meningomyelitis was made. With acyclovir and foscarnet sodium therapy, repeated CSF studies revealed normal cell count and protein. No atypical cells were found. The repeated brain MRI also revealed obvious resolution of the previous abnormal pachymeningeal enhancement. Conclusion This case highlights the importance of recognizing the unusual phenomenon of traditional tests in VZV meningoencephalitis with meningomyelitis, and timely using of further precise examinations to detect viral DNA, which is required to prevent missed diagnosis.